“Values can be taught through Physical Education” – narratives of Singapore’s Beginning Physical Education Teachers (BPETs) - Muhammad Shufi Bin Salleh; Lynnette Krystall G Aviado (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2023)
Previous studies have emphasized the potential of using Physical Education (PE) as a platform to teach values. However, few teachers are deliberate in their attempts to teach values through PE as many may not have the teaching strategies to achieve the affective learning outcomes. What is unknown currently is the starting point of newly trained PE teachers, specifically in Singapore’s context, Beginning Physical Education Teachers (BPETs), on their preparedness to teach in the affective learning domain. The purpose of the study is to listen to the “lived experiences” of BPETs through interviews on their strategies and challenges to incorporate the teaching of values in their classroom. Three BPETs (2M, 1F) with no more than 3 years of teaching experience from primary and secondary schools were invited to participate in the study. Individual interviews were conducted and transcribed verbatim. The transcript was analysed using thematic analysis. The findings highlighted three common themes: 1. PE being a platform to see values in action; 2. Discussion on values and what it means in students’ lives; and 3. Reflection on their BPET journey. The findings show that BPETs believe that values can be taught through PE, and they would attempt to teach values in explicit or implicit ways. However, some teachers suggested specific courses that could equip them with the strategies to teach values specifically in a PE setting. Future studies can consider interviewing senior PE teachers on their experiences and strategies teaching values through PE.